KINERJA PEGAWAI ASN DALAM MENJALANKAN TUGAS POKOK DAN FUNGSI (TUPOKSI) BAPPEDA KOTA PEKANBARU - Wulandari Muchtar; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Pekanbaru City Regional Development Planning Agency is a supporting element of the Pekanbaru City Government in the planning field. The importance of employee performance at the Pekanbaru City Planning and Development Agency (Bappeda) which has the main task of assisting the Mayor in administering Pekanbaru City Government in the field of development planning, and play a role as a regional technical institution that is responsible for development planning as mandated in Article 14 paragraph 1 of Law Number 32 Year 2004 concerning Regional Government. The purpose of this study was to determine and analyze the performance of ASN employees in carrying out the main tasks and functions of Pekanbaru City Bappeda and to identify and analyze the factors inhibiting the performance of ASN employees in carrying out the main duties and functions of the Pekanbaru City Bappeda. Employee performance appraisal indicators consist of quantity, quality, time and cost. The results of this study indicate that employee performance based on the output aspect in the aspect of work quantity is good enough, but what is targeted has not been achieved so it is still necessary to improve management and organizational communication. In the aspect of work quality it is still not satisfactory because the quality of work results is still low, in the aspect of employee consistency it shows that employees are still not consistent in carrying out their work, and in the aspect of employee attitudes, they are also still not satisfied which is reflected in the lack of discipline towards time. Keywords: Performance, Employees, Bappeda.